Key dimensions of city brand personality of Melaka Historic City, Malaysia - Ahmad, Muhamad Fazil (2015)
A city can seek to take a particular brand personality through various branding strategies. Nevertheless, people may interpret the communicated messages through the prism of their perceptual experiences and, therefore, might react differently to a brand message as to what it was initially designed for. This research attempts to understand a measure on city branding pertaining to Melaka based on the Aaker’s brand personality scale. The study specifically proposes the key dimensions of a city brand personality in promoting Melaka Bandaraya Bersejarah (Historic City) through its strategic communication campaign. Political instability, a decline of public trust in the government and an environmental pollution are some of the issues concerned in the development of a city branding in the state of Melaka. Theoretically, little attention has been given to the application of brand personality in city branding in Asia as a whole, and specifically in Malaysia. The current study in four phases, employed quantitative methods and was conducted entirely in Melaka City. The following methods were used in the data collection: library research method, descriptive survey and structured interview. In the first phase, library research and expert interview methods were used to secure a comprehensive yet appropriate dictionary of terms by collecting and compiling synonyms of Aaker’s (1997) five brand personality dimensions. In the second phase, a pre-test study was conducted to identify and verify the key dimensions of city branding. In the third phase, a survey using questionnaires (the main study) was employed applying Aaker’s brand personality scale. Finally, in the fourth phase, structured interviews were conducted to complement the results of the main study. Using structural equation modelling, the study investigated a model fit for city-brand personality dimensions of Melaka City. The results showed that ‘size ruggedness’ originally developed by Aaker, was not reliable or valid, while the other four dimensions were refined using a confirmatory factor analysis and structural equation model. The factors were named ‘Peacefulness’(factor 1), ‘Malignancy’ (factor 2), ‘Sophistication’ (factor 3), ‘Uniqueness’ (factor 4) and ‘Conservatism’ (factor 5). Compared to Aaker’s scale, the “Sophistication” dimension was retained in two items: “Glamorous” and “Charming”. “Ruggedness” was not retained in the Malaysian context. The “Sincerity” dimension was narrowed down to “Peacefulness”, “Competence” to “Malignancy” and “Excitement” to “Uniqueness”. Thus, it seems the scale of 24 items brand personality to work better in the city branding among internal stakeholders (opinion leaders, communication managers, executives and non-executive officers). Theoretically, this study contributes to the existing literature (Communication) on brand personality as well as touches upon the theories of brand identification, preference and trust. The results of this study have a similar meaning in Japan, the United States (USA), Chile, Russia, Turkey and Spain especially in ‘sophistication’ dimension. The finding also proposes brand personality may indeed reflect the Neuroticism (Emotional Stability) dimensions of the “Big Five Model”. Essentially, the results showed that the revised brand personality is in dire need of being tailored to Asian values. In fact, this study revealed that a cultural component is a strong predictor of brand personality. Perhaps a measure can be employed as a policy by policymakers to re-brand Melaka City strategically. The substantial contribution of this study is the city brand personality has been successfully developed in a Malaysian context. Thus, this study may enrich current literature on branding and city branding, specifically in the Asian context. Keywords: Brand Personality, City Brand Personality, City Branding, City Image, Melaka City.